2019
DOI: 10.21608/jesp.2019.68282
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and Vascular Changes in Trichinella Spiralis in Fected Mice After Parenteral Artemether Treatment

Abstract: Trichinosis is a parasitic disease, caused by a nematode worm of the genus Trichinella. Infection is caused by ingestion of undercooked contaminated meat with infective parasitic larvae. The study assessed the muscle apoptotic and vascular changes in T. spiralis infected mice after intra-muscular artemether injection. This study included 80 clean laboratory-bred Swiss albino mice orally infected with 200 T. spiralis larvae/mouse. Four groups of mice (20 mice each), GI: non-infected (control normal); GII: infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In our study, CD34 was markedly expressed in the small intestine, skeletal muscle and heart of infected non-treated mice. Ibrahim et al (2019) demonstrated the increased expression of CD34 in myoendothelial cells around encysted larvae in skeletal muscle of T. spiralis-infected mice, which was efficiently reduced by the administration of artemether. In the current study, the administration of curcumin lead to a significant decrease in CD34 expression in all tissue samples.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, CD34 was markedly expressed in the small intestine, skeletal muscle and heart of infected non-treated mice. Ibrahim et al (2019) demonstrated the increased expression of CD34 in myoendothelial cells around encysted larvae in skeletal muscle of T. spiralis-infected mice, which was efficiently reduced by the administration of artemether. In the current study, the administration of curcumin lead to a significant decrease in CD34 expression in all tissue samples.…”
Section: Discussionmentioning
confidence: 96%
“…T. spiralis up-regulates VEGF by stimulating thymosin β4 [ 17 , 57 ]. In Ibrahim et al [ 58 ] study on experimental muscular trichinosis, enhanced CD34 expression in myoendothelial cells was observed around the encysted larvae, which was subsequently reduced following administration of artemether. While in Fu et al [ 59 ] research, curcumin was reported to interfere with VEGF – VEGF receptor 2 signaling pathway resulting in reduced VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Also, weak expression of BcL-2 in early infection followed by strong positive staining for mitochondrial related genes as BAX (a pro-apoptotic member of BcL-2 family) in cellular infiltrates around capsule of encysted larvae. This was explained due to replacement of destructed mitochondria as a result of parasite invasion with new one (28)(29)(30) .…”
Section: Discussionmentioning
confidence: 99%